THE IMPORTANCE OF STUDYING ABDULLAH AVLONI'S ENLIGHTENED VIEWS IN ACHIEVING THE THIRD RENAISSANCE - Rakhimjonova Dilfuza (Journals Park Publishing, 2023)
This article is about the importance of studying the life and work of Abdullah Avloni and his enlightened views in achieving the Third Renaissance.
Keywords: Mergancha mahalla, educatedfamily, Third Renaissance, strengthen love, shape worldview, students, approaches, culture, enlightenment.